Towards detection of early response in neoadjuvant chemotherapy of breast cancer using Bayesian intravoxel incoherent motion - Cheung, Sai Man; Wu, Wing-Shan; Senn, Nicholas; Sharma, Ravi; McGoldrick, Trevor; Gagliardi, Tanja; Husain, Ehab; Masannat, Yazan; He, Jiabao (Frontiers in Oncology, 2023)
The early identification of good responders to neoadjuvant chemotherapy (NACT) holds significant potential in the optimal treatment of breast cancer. Recent Bayesian approach has been postulated to improve the accuracy of intravoxel incoherent motion (IVIM) model for clinical translation. This study examined the prediction and early sensitivity of Bayesian IVIM to NACT response.Materials and Methods: Seventeen female patients with breast cancer were scanned at Baseline and sixteen patients after Cycle 1. Tissue diffusion and perfusion from Bayesian IVIM were calculated at Baseline with percentage change at Cycle 1 computed with reference to Baseline. Cellular proliferative activity marker Ki-67 was obtained semi-quantitatively with percentage change at excision computed with reference to core biopsy.The perfusion fraction showed a significant difference (p=0.042) in percentage change between responder groups at Cycle 1, with a decrease in good responders (-7.98% (-19.47 -1.73), n=7) and an increase in poor responders (10.04% (5.09 -28.93), n=9). There was a significant correlation between percentage change in perfusion fraction and percentage change in Ki-67 (p=0.042). Tissue diffusion and pseudodiffusion showed no significant difference in percentage change between groups at Cycle 1, nor significant correlation against percentage change in Ki-67. Perfusion fraction, tissue diffusion and pseudodiffusion showed no significant difference between groups at Baseline, nor significant correlation against Ki-67 from core biopsy.The alteration in tumour perfusion fraction from Bayesian IVIM model, with association to cellular proliferation, showed early sensitivity to good responders in NACT.